2022
DOI: 10.52787/agl.v52i2.179
|View full text |Cite
|
Sign up to set email alerts
|

Erradicación de primera línea de Helicobacter pylori con terapia dual de altas dosis versus terapia cuádruple con bismuto por 14 días: estudio multicéntrico, prospectivo y aleatorizado

Abstract: Introducción. Ante la alta prevalencia de infección por Helicobacter pylori a nivel mundial y la gran resistencia de esta bacteria a los antibióticos, se ha hecho necesario el uso de terapias más agresivas para erradicar la infección. Por esta razón se propone el uso como primera línea de una terapia dual ampliada frente a la terapia cuádruple convencional utilizada para el tratamiento de esta patología.  Objetivos. Evaluar y comparar la eficacia y seguridad de la terapia cuádruple con bismuto (TCB) contra la … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Table 3 shows similar studies carried out with dual therapy in other populations. A recent study conducted in Colombia, which included patients with dual therapy, showed eradication rates similar to those observed in our study 17 . Eradication relieves symptoms, prevents complications, and reduces transmission, improving patient well‐being and reducing healthcare burden.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Table 3 shows similar studies carried out with dual therapy in other populations. A recent study conducted in Colombia, which included patients with dual therapy, showed eradication rates similar to those observed in our study 17 . Eradication relieves symptoms, prevents complications, and reduces transmission, improving patient well‐being and reducing healthcare burden.…”
Section: Discussionsupporting
confidence: 89%
“…The high eradication success rate of HDDT in our study could be attributed to the following factors 1 : in Chile, the rate of resistance to amoxicillin is 4.2%, lower than clarithromycin resistance 21 . In the Eastern Mediterranean and Americas Region, the prevalence of primary amoxicillin resistance was relatively high, accounting for approximately 14% and 10% respectively, 22 this could reduce the efficacy of this therapy in the eradication of H. pylori 2 ; higher dosing frequency of the PPI dose (three times daily) has been associated with longer lasting anti‐acidic effects 23 . H. pylori has been shown to be more sensitive to antibiotics, when the gastric pH value is higher than six 3,24 ; the effect of PPI on inhibiting gastric acid secretion is affected by CYP2C19 gene polymorphism.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Of the 42 reports selected for detailed evaluation, 22 studies were excluded because of non-RCT (n = 1), using interventions that did not meet the criteria (n = 16), with insufficient data for analysis (n = 1), using antibiotics that were considerably different from other included studies (n = 2), and duplicates (n = 2). Finally, 20 studies [19][20][21][22][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] including 7891 patients were eligible for our systematic review and meta-analysis. The article selection process is illustrated in…”
Section: Description Of the Studiesmentioning
confidence: 99%